Pelatihan Teknik Umpan Tinggi dalam Sepak Takraw Untuk Meningkatkan Keterampilan Bermain PSTB Batu Noni Kec.Anggeraja Kab.Enrekang - Suherdandi Suherdandi; Khalid Rijaluddin; Andi Temmassonge; Maria Herlinda Dos Santos; Rahmat Ilahi; Andi Ogo Darminto (Jurnal Pengabdian Masyarakat Waradin, 2024)
Sepak takraw is a big ball game that combines the techniques of football, volleyball and badminton. This activity aims to introduce and train PSTB Batu Noni youth's playing skills in making high passes in the sepak takraw game. During this activity, the author used a participatory approach with a combination of theory and practice between activities and games at the end of each activity. The activity is aimed at people who are members or active in the sepak takraw sport of the Batu Noni Sepak Takraw Association (PSTB). Warming up, weighing the ball, passing in pairs, practicing high passes near the net are things that are very important. The use of variations in training can improve the quality of passing training and can foster excitement and motivate players in training. to do in the process of practicing high passes in sepak takraw. In this activity, PSTB players have improved their skills in playing sepak takraw. This activity or training is put to good use by PSTB players in training and improving their playing techniques, especially high passing techniques. This activity or training is always used by sepak takraw coaches in training their athletes.